2019
DOI: 10.1161/circinterventions.118.007494
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Pattern of Disease Assessed by Pressure-Wire Pullback Has an Influence on Fractional Flow Reserve/Instantaneous Wave-Free Ratio Discordance

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 21 publications
2
37
0
1
Order By: Relevance
“…27 37 49 88 Most data on discordance currently exist on the comparison between iFR and FFR, with discordance believed to occur ~15%-20% of lesions, particularly in those subtending large areas of myocardium, that is, LMCA and proximal LAD. 49 89 Other areas where discordance has been identified include the pattern of coronary disease (focal vs diffuse), 90 and patient characteristics such as gender, presence of diabetes mellitus and beta blocker use. [91][92][93][94] A summary of these discordant groups associated with FFR and iFR is presented in table 2.…”
Section: Controversies In the Use Of Nhprmentioning
confidence: 99%
“…27 37 49 88 Most data on discordance currently exist on the comparison between iFR and FFR, with discordance believed to occur ~15%-20% of lesions, particularly in those subtending large areas of myocardium, that is, LMCA and proximal LAD. 49 89 Other areas where discordance has been identified include the pattern of coronary disease (focal vs diffuse), 90 and patient characteristics such as gender, presence of diabetes mellitus and beta blocker use. [91][92][93][94] A summary of these discordant groups associated with FFR and iFR is presented in table 2.…”
Section: Controversies In the Use Of Nhprmentioning
confidence: 99%
“…Because FFR requires the induction of a high flow state (hyperemia), it tends to be more sensitive to separation forces (where flow is squared), found with more focal lesions. This association was recently confirmed in a pressure wire pullback study, where iFR−/FFR+ discordance was more frequently associated with predominantly focal disease (59%, 24/41), while iFR+/FFR− disease was more often diffuse (82%, 31/38; p < .001 for difference). Considering that PCI tends to be more useful for focal disease, such data arguably favors the use of FFR in situations of iFR−/FFR+ discordance.…”
Section: Postulated Mechanisms Of Ifr/ffr Discordancementioning
confidence: 63%
“…Separation and frictional components of pressure loss diagram (from Warisawa et al) [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Postulated Mechanisms Of Ifr/ffr Discordancementioning
confidence: 99%
“…Several studies this year attempted to examine the physiological characteristics of lesions with discordant FFR and iwFR and identify lesion types and subgroup of patients where FFR should be preferred to iwFR and vice versa. (37,38) A recent subanalysis of the Functional Lesion Assessment of Intermediate Stenosis to Guide Revascularisation (DEFINE-FLAIR) study comparing outcomes in patients with a lesion in the left anterior descending coronary artery deferred from revascularisation based on the FFR or iwFR estimations showed a lower event rate in the iwFR group at 1-year follow-up that was attributed to a lower incidence of unplanned revascularisations (2.22% vs. 4.99%, p=0.03). (39) Conversely, a post hoc analysis of the same study in diabetic patients showed no differences in outcomes between the FFR and iwFR groups (7.2% vs. 10.0%; p=0.30); however, the incidence of non-fatal MI was higher in the iwFR group (4.7% vs. 1.9%; p=0.05), with a significant interaction for the presence of diabetes (p=0.04).…”
Section: Coronary Physiologymentioning
confidence: 99%